A bronsted basic ionic liquid as an efficient and environmentally benign catalyst for biodiesel synthesis from soybean oil and methanol. Issue 18 (16th September 2016) - Wang, Lu-Lu; Zhang, Yang; Zhang, Fan; Feng, Ruijiang
ABSTRACT: Morpholine basic ionic liquid was synthesized with N-methyl morpholine, N-butyl bromide, and KOH by two-step method and was used to catalyze the transesterification of soybean oil with methanol to biodiesel. The structure of the catalyst were examined by 1 H nuclear magnetic resonance. The effects of the molar ratio of methanol to oil, reaction temperature, and amount of catalyst on the biodiesel yield were investigated. Optimized biodiesel yield of 94.5% was achieved with catalyst amount of 3.0 wt%, and methanol to soybean oil molar ratio of 14:1 at reaction temperature of 60 °C for 6 h. The catalyst has maintained sustained activity after being employed to six cycles. The prepared biodiesel component was analyzed by gas chromatography-mass spectrometry (GC-MS) and the results showed that the biodiesel comprised of hexadecanoic acid methyl ester, 10, 13-octadecadienoic acid methyl ester, 9-octadecenoic acid methyl ester, and octadecanoic acid methyl ester, illustrating that fatty acids of soybean oil were converted completely.